Mediation of Domestic Conflict in Divorce Cases at Religious Courts in Banten Province - Rusli, Deni; As-Syafe’i, Zakaria; Zaini, Ahmad; Tarihoran, Naf’an (Faculty of Sharia and Islamic Law Institut Agama Islam Negeri Bone, 2025)
In running a household, no one is free from domestic conflicts. These domestic conflicts are caused by various factors, which ultimately lead to the filing of divorce cases in the Religious Court, either through talak or gugat. These cases can be resolved through mediation in various forms. This research aims to analyze the effectiveness of mediation in resolving domestic conflicts in divorce cases at the Religious Court in Banten Province. The research method employed is qualitative research with a juridical approach, utilizing data collection techniques that include observation and document study. The results show that mediation plays a significant role in reducing the divorce rate by providing couples with a space to dialogue and seek reconciliation solutions. However, various obstacles such as the psychological unpreparedness of the couples, family pressure, and a lack of understanding of the mediation concept often hinder the success of mediation. Juridically, mediation has been carried out by the applicable regulations. This is evident from the procedures followed during the mediation process based on the regulations governing it, but mediation conducted in the Religious Court in Banten Province still experiences many failures. Therefore, efforts are needed to improve the quality of mediation through mediator training, socialization regarding the benefits of mediation, and psychological support for couples facing marital conflict.